Imaging alterations due to squamous metaplasia in intracranial neurenteric cysts: A report of two cases. Issue 3 (June 2016) - Watanabe, Nobuyuki; Akasaki, Yasuharu; Fujigasaki, Junko; Mori, Ryosuke; Aizawa, Daisuke; Ikeuchi, Satoshi; Murayama, Yuichi
Intracranial neurenteric cysts are rare congenital abnormalities with a broad imaging spectrum, and therefore are occasionally mistaken for other common intracranial cysts such as epidermoid and arachnoid cysts. We report two cases of neurenteric cysts in the posterior cranial fossa that were initially mistaken for other types of cysts. They exhibited signal intensity alterations in magnetic resonance imaging with significant volume expansion during their long-term observation. Both cases received surgical treatment because of clinical deterioration. Histologically, the cysts were lined by flattened or cuboidal epithelium, occasionally showing squamous metaplasia. Xanthogranulomatous inflammation and accumulation of cholesterol clefts, dry keratin and proteinaceous substance were observed in the cysts. These findings may indicate that chronic inflammation in neurenteric cysts induces squamous metaplasia, keratinization and high proteinaceous content, and causes MRI signal intensity alterations and volume expansion. We propose that MRI signal intensity alterations in neurenteric cysts may be a warning sign of their volume expansions, and thus require closer follow-up imaging and eventually surgical treatment.